EVALUATION OF THE POLICY ON THE FORMATION AND RECRUITMENT OF MANAGEMENT OF THE MERAH PUTIH VILLAGE/SUB-DISTRICT COOPERATIVE - Jusip (International Journal of Multidisciplinary Reseach, 2026)
The accelerated formation of the Merah Putih Village/Sub-district Cooperative has raised fundamental issues. The cooperative's administrative structure was quickly established, but the recruited administrators were not necessarily capable of running the business, creating a gap between legality and operationalization. This study aims to evaluate the policy of establishing and recruiting cooperative administrators in North Kalimantan Province. The study employed a qualitative approach with an evaluative design based on William Dunn's six policy evaluation criteria. The study population was cooperative stakeholders in North Kalimantan, while the sample consisted of nine informants selected purposively in Tarakan, Nunukan, and Tana Tidung. Informants included government officials, village and sub-district heads, administrators, supervisors, assistants, and members. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques. The results showed that administrative achievement was high, but operational achievement was still limited. Recruitment through deliberation was legitimate, but not accompanied by standardized competency assessments. Coaching for administrators is also inadequate, and policy accuracy depends heavily on adaptation to local conditions. Research concludes that the quality of the recruitment process determines the success of the policy. Therefore, the government needs to establish minimum competency criteria, map the initial competencies of administrators, conduct practice-based training, provide appropriate mentoring, and shift the measure of success from mere establishment to functioning.